An integrative approach to characterize Malagasy bats of the subfamily Vespertilioninae Gray, 1821, with the description of a new species of Hypsugo. (April 2015) - Goodman, Steven M.; Rakotondramanana, Claude Fabienne; Ramasindrazana, Beza; Kearney, Teresa; Monadjem, Ara; Schoeman, M. Corrie; Taylor, Peter J.; Naughton, Kate; Appleton, Belinda
Abstract : Although important advances have been made in recent years in the taxonomy of different families and subfamilies of Malagasy bats, those belonging to the Vespertilioninae remain partially unresolved. Herein using a mitochondrial marker (cytochrome b ) as the point of departure for 76 specimens of Malagasy vespers and appropriate African taxa, we diagnose the six taxa of this subfamily on the island by overlaying different morphological and bioacoustic characters on the clade structure of sequenced animals. The species include: endemic Neoromicia matroka, which is sister to African N . capensis ; endemics N . malagasyensis and N . robertsi, which form sister species; a member of the genus Hypsugo, which is sister to African H . anchietae and described herein as new to science; Pipistrellus hesperidus for which Madagascar animals are genetically close but distinct from African populations of the same species; and endemic P . raceyi, which shows segregation of eastern (mesic) and western (dry) populations and its sister species relationships are unresolved. While the external and craniodental measurements, as well as bioacoustic variables, allow only partial differentiation of these six species of Vespertilioninae, molecular characters provide definitive separation of the taxa, as do male bacular morphology. © 2015 The Linnean Society of London